Isolation and characterization of ten novel microsatellite loci in the red-winged tinamou (Rhynchotus rufescens, Tinamiformes, Aves) and cross-amplification in other tinamous - Santos, Dimas O. [UNESP]; Moreira, Lucas R.; Tonhati, Humberto [UNESP]; Caparroz, Renato (Springer, 2012)
We describe the isolation and characterization of ten microsatellite loci from the red-winged tinamou (Rhynchotus rufescens) and also evaluated the cross-amplification of these loci and other ten loci previously developed for the great tinamou (Tinamus major) in other tinamous. Genetic variability was assessed using 24 individuals. Six loci were polymorphic with moderate to high number of alleles per locus (2-12 alleles) and showed expected heterozygosity (HE) ranging from 0.267 to 0.860. All loci conformed to the Hardy-Weinberg expectation and linkage disequilibrium was not significant for any pair of loci. This battery of polymorphic loci showed high paternity exclusion probability (0.986) and low genetic identity probability (4.95 x 10(-5)), proving to be helpful for parentage tests and population analyses in the red-winged tinamou. The cross-amplification was moderate where of the 160 locus/taxon combinations, 46 (28.75%) successfully amplified.
Keywords: Microsatellite; Neotropical; Rhyncothus rufescens; Tinamiformes; Tinamous